EGYPTIAN NEGOTIATIONS ON THE FILLING AND OPERATION OF THE GRAND ETHIOPIAN RENAISSANCE DAM PROJECT - Minasari, Arofah; Salsabila, Yasmin Raudhah (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Egypt is negotiating with Ethiopia regarding the construction of the Grand Ethiopian Renaissance Dam (GERD) on the Nile River. This research employs Negotiation theory combined with the role of power and Transboundary Water Interaction concept to understand the negotiation process Egypt carried out. The research findings show that Egypt, using its power that comprises material, bargaining and ideational power, tries to maintain its hegemony in the region. Egypt succeeded in inviting third parties such as the US, World Bank and UNSC in the negotiation process. Political dynamics in the region and internal instability after the 2011 Egyptian Revolution influenced Egypt's strength in its negotiations with Ethiopia. Thus, the interaction is related to contest and compliance. The development of GERD in Ethiopia is seen as a contest for the hegemonic situation, while Egypt is trying to create compliance with Ethiopia. Egypt seeks to create compliance with the status quo through some mechanisms: coercive, utilitarian, normative, and ideological hegemonic. Although the two countries compete with and obey each other, they still collaborate and negotiate to resolve the GERD problem. The interaction between these two during the negotiation process can be categorized as a neutral interaction with low conflict–low cooperation category.